Issues relating to selective reporting when including non‐randomized studies in systematic reviews on the effects of healthcare interventions. (13th November 2012) - Norris, Susan L; Moher, David; Reeves, Barnaby C; Shea, Beverley; Loke, Yoon; Garner, Sarah; Anderson, Laurie; Tugwell, Peter; Wells, George; Reeves, Barnaby C.; Wells, George A.
<x xml:space="preserve">Abstract</x> Background Selective outcome and analysis reporting (SOR and SAR) occur when only a subset of outcomes measured and analyzed in a study is fully reported, and are an important source of potential bias. Key methodological issues We describe what is known about the prevalence and effects of SOR and SAR in both randomized controlled trials (RCTs) and non‐randomized studies (NRS), and the effects of SOR and SAR on summary effect estimates and conclusions in systematic reviews of the effectiveness of healthcare interventions. Guidance Review authors should always suspect SOR and SAR in reviews that include NRS, assess primary studies for the risk of bias, and make reasonable attempts to retrieve study protocols or other documentation developed before study recruitment began. There are clues that may suggest SOR or SAR in NRS, including differences between the methods and results sections of the publication, study funder, and differences between study protocol or registration information and the study report. Conclusion Existing evidence about reporting biases in primary studies comes almost exclusively from methodological reviews of RCTs. The prevalence and impact of SOR and SAR in NRS are likely even greater than in RCTs but it is difficult to identify and confirm selective reporting in NRS. Copyright © 2012 John Wiley & Sons, Ltd.